اليقظة الاستراتيجية ودورها في جودة الأداء المؤسسي: بحث تحليلي تطبيقي في دائرة تسجيل الشركات في وزارة التجارة العراقية (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to explain the nature of the correlations and influence between strategic vigilance and the quality of institutional performance in the department under study. The hypotheses of this research were tested in the company registration department, as it provides its services to a wide segment of society, and introducing the dimensions of strategic vigilance into its work and making improvements in it will serve this segment. Broad, as the relationship between the research variables was clarified through the formulation of some main and subsidiary hypotheses. The research sample included senior and middle management in the organization under investigation, and data was collected from (35) individuals holding the following administrative positions (general manager, assistant general manager, department head). , assistant department director, division official), who have decision-making authority in the organization, and the questionnaire was adopted as the main tool for collecting data related to the research, which included (44) paragraphs that dealt with the dimensions of the two research variables, as they were prepared based on a five-point Likert scale, and the answers were analyzed to reach To the final results of the research through the use of ready-made statistical programs (SSPS), the statistical methods used in the analysis are descriptive statistics methods (weighted arithmetic mean, standard deviation, and coefficient of variation) in determining the strength of the research variables, and inferential statistics methods (correlation coefficient, simple linear regression (and testing via a matrix), the current research reached a number of conclusions, the most important of which is the existence of a correlation and impact of strategic vigilance with its sub-dimensions on the quality of institutional performance. This indicates the possibility of spreading the culture of strategic vigilance in the investigated department, by consolidating strategic vigilance with its sub-dimensions (environmental, technology, Commercial, competitive) in its work, by educating employees about the importance of this approach in enhancing the quality of institutional performance and improving the service reality of the organization